A new species of Wohlfahrtia Brauer & Bergenstamm (Diptera: Sarcophagidae) from northwestern China, with three new synonymies and a pictorial synopsis - Ge, Ying-Qiang; Zhang, Dong; Thomas, Pape (Zootaxa, 2018)
A new species, Wohlfahrtia spinisternum Pape & Zhang sp. nov., is described based on one male specimen collected from the arid steppe habitat of Kalamaili Nature Reserve, Xinjiang, China. The species shares with W. aschersoni (Enderlein, 1934) a reduction of the distal posteroventral row of flattened, spiny bristles (‘ctenidium’) on the male mid femur, and has male sternite 5 gradually raised posteriorly into a pointed process, which is a unique feature in the entire subfamily Paramacronychiinae. Lectotypes are designated for Wohlfahrtia musiva Séguy, 1953 and Wohlfahrtia triquetra Séguy, 1933, and three new synonymies are proposed: Wohlfahrtia longicorpuris Mawlood & Abdul-Rassoul, 2001 syn. nov. of W. nuba (Wiedemann, 1830), Wohlfahrtia musiva Séguy, 1953 syn. nov. of W. villeneuvi Salem, 1938, and Wohlfahrtia triquetra Séguy, 1933 syn. nov. of W. indigens (Wiedemann, 1830). A pictorial synopsis of male terminalia of the 24 recognized species of Wohlfahrtia Brauer & Bergenstamm, 1889 is provided.